Using Home-Cage Monitoring to Determine the Impact of Timed Mating on Male Mouse Welfare - Moore, Joanna L.; Brook, Eloisa I. (Frontiers in Neuroscience, 2022)
Some of our breeding programmes include the use of Prm1 male Homozygous mice which are naturally sterile. This removes the need to use vasectomised males to induce pseudopregnancy in female mice. These males can be kept for up to nine months and are housed with a companion female. During the timed mating period the companion female is replaced with a new female. This procedure can occur at regular intervals causing a significant increase in cage activity; one of our objectives was to determine whether this was as a result of timed mating. We wanted to investigate the disruption caused to mice during the day of the swap and how long it would take for the cage activity to return to pre-replacement baseline levels. We hypothesized that this impact would be reflected as a significant increase in cage activity, which in itself may not be a result of a negative experience but the potential of repeated disruption to their activity pattern should be considered. We used a well-known home-cage monitoring system to assess changes to the activity pattern in cages when a companion female is replaced. Data from our initial study showed that in the two-hour period after the female is replaced there is a significant increase in cage activity compared to the same time frame on the previous day. In the subsequent study, where no cage change occurred, an increase in activity was also observed when females were replaced; this returned to baseline after approximately four hours. Prolonged activity during the rest period of mice (over two hours) could lead to them being fatigued during their active period; therefore, as a refinement we propose that timed matings be performed later in the day, at a time when the animals are active.